Intelligibility and comprehensibility of the Filipino English accent to Hong Kong English speakers - Li, Hui Ping; Chen, Hsueh Chu (Penerbit Universiti Kebangsaan Malaysia, 2019)
Intercultural communication between Hong Kong people and Filipinos is common and crucial in Hong Kong as Filipinos are the largest non-local ethnic group, and Filipino domestic helpers play a significant role in households and childcare. This study investigated the phonological patterns of Filipino English and explored the intelligibility and comprehensibility of the English spoken by Filipino domestic helpers to student teachers of English in Hong Kong. By analysing the speech produced by three Filipino English speakers, features of Filipino-accented English were identified. Moreover, by conducting listening-dictation tasks, it was found that the listeners considered 30% and 80.6% of the isolated words and keywords in a passage respectively to be intelligible, and 74.7% of the speech produced by Filipino English speakers was comprehensible. The major types of features of the Filipino English accent, which are also found to be factors which contribute to problems in intelligibility and comprehensibility such as consonant substitutions, deletion of consonants and consonant clusters, no distinction between long and short vowels, replacement of vowels, and shifting of word stress, are discussed in detail in this research paper along with the pedagogical and social implications.